1977
DOI: 10.1093/jnci/59.5.1401
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Acyclic and Cyclic N-Nitrosamines in Cultured Human Bronchi2

Abstract: The metabolism of carcinogenic N-nitrosamines was studied in normal-appearing bronchial specimens obtained from 4 patients. Explants of bronchi were cultured in a chemically defined medium for 7 days. N-Nitrosamines [N-nitrosodimethylamine (DMN), N-nitrosodiethylamine (DEN), N,N'-dinitrosopiperazine (DNP), N-nitrosopyrrolidine (NPy), and N-nitrosopiperidine (NPd)] labeled with 14C were each then added at 100 mumoles for 24 hours. Measurable CO2 was formed by bronchial explants from: 1) DMN, DEN, and NPy in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Retention times of these peaks in our system corresponds to tetrols (Fig 2). The third major peak from epithelial cells co-elutes with the standard 9,lO-dihydrodiol of BaP and, based on the work of others [35,36], could also contain a triol. Formation of this latter metabolite seems unlikely by epithelial cells as no evidence for other isomeric forms of the trihydroxy-BaP derivatives was noted (Fig 2).…”
Section: Identification Of Unconjugated Metabolitesmentioning
confidence: 86%
See 2 more Smart Citations
“…Retention times of these peaks in our system corresponds to tetrols (Fig 2). The third major peak from epithelial cells co-elutes with the standard 9,lO-dihydrodiol of BaP and, based on the work of others [35,36], could also contain a triol. Formation of this latter metabolite seems unlikely by epithelial cells as no evidence for other isomeric forms of the trihydroxy-BaP derivatives was noted (Fig 2).…”
Section: Identification Of Unconjugated Metabolitesmentioning
confidence: 86%
“…In addition, the fact that 85-90 per cent of all human cancer is of epithelial cell origin makes apparent the importance of an epithelial system for carcinogenic investigations. Studies of chemical carcinogenesis have been conducted in a wide variety of human epithelial organs in culture [14,36,. Such studies are hampered by wide sample variation and, more important to our understanding of carcinogenic mechanisms, by the mixture of cell types present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These agents interact with DNA to form stable adducts such as alkylated purine and pyrimidine bases (Doniger et al, 1985;Fong et al, 1979;Van Bentham et al, 1992). Metabolic studies of explant cultures of esophageal tissues have shown that the human and rat esophagi are fully capable of converting nitrosamines into metabolities that alkylate DNA at the N 7 and O 6 positions of guanine (Antrup and Stoner, 1982;Harris et al, 1979). O 6 -methylguanine persists, accumulates and leads to DNA mutations as previously demonstrated in esophageal squamous papillomas in nitrosamine treated rats (Siglin et al, 1996).…”
Section: Introductionmentioning
confidence: 84%
“…The mean binding level in specimens from patients with glandular, mucous differentiated cancers was not significantly different from controls. The metabolism of both cyclic and acyclic N-nitrosamines was assessed in human bronchial organ cul-tures and these compounds were found to be metabolized to products which bound to cellular DNA (54). The capacity of human bronchus to activate aflatoxin B1 to derivatives which bind to DNA also was determined; the values obtained were somewhat lower than with BP (55).…”
Section: Carcinogen Metabolism and Binding In Human Respiratory Tissuesmentioning
confidence: 99%